2022
DOI: 10.5498/wjp.v12.i9.1127
|View full text |Cite
|
Sign up to set email alerts
|

Emerging role of psychosis in Parkinson's disease: From clinical relevance to molecular mechanisms

Abstract: Parkinson’s disease (PD) is the second most common neurodegenerative disease. Psychosis is one of the common psychiatric presentations in the natural course of PD. PD psychosis is an important non-motor symptom, which is strongly correlated with a poor prognosis. Increasing attention is being given to PD psychosis. In this opinion review, we summarized and analyzed the identification, screening, epidemiology, mechanisms, risk factors, and therapeutic approaches of PD psychosis based on the current clinical evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 110 publications
(125 reference statements)
0
1
0
Order By: Relevance
“…In 2002, the European Agency for the Evaluation of Medicinal Products (EMEA) approved Clozapine for the treatment of psychotic symptoms in patients with Parkinson's Disease (PD) after failure of standard treatments [30]. Indeed, about 25-30% of Parkinson's patients experience psychotic symptoms, with a constant increase linked to the duration of illness and a great impact on quality of life [87]. The indication was mainly supported by data from the Parkinson Study Group of 1999 and by the FDA's Orphan Drug Division, which demonstrated a reduction in symptoms, by 9.3 points vs. 2.6 points with placebo, with Clozapine at a mean dose of approximately 25 mg/day, as confirmed by subsequent studies [29,[88][89][90][91].…”
Section: Psychiatric Disease In Comorbidity With Parkinson's Diseasementioning
confidence: 99%
“…In 2002, the European Agency for the Evaluation of Medicinal Products (EMEA) approved Clozapine for the treatment of psychotic symptoms in patients with Parkinson's Disease (PD) after failure of standard treatments [30]. Indeed, about 25-30% of Parkinson's patients experience psychotic symptoms, with a constant increase linked to the duration of illness and a great impact on quality of life [87]. The indication was mainly supported by data from the Parkinson Study Group of 1999 and by the FDA's Orphan Drug Division, which demonstrated a reduction in symptoms, by 9.3 points vs. 2.6 points with placebo, with Clozapine at a mean dose of approximately 25 mg/day, as confirmed by subsequent studies [29,[88][89][90][91].…”
Section: Psychiatric Disease In Comorbidity With Parkinson's Diseasementioning
confidence: 99%